(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the potential of artificial intelligence (AI) technologies in public health monitoring and the emerging privacy issues. AI is an effective tool for early detection of epidemics, tracking the spread of disease, and effectively managing health resources. At the same time, a number of problems related to personal privacy and data security arise during data collection and processing. The article highlights the importance of anonymization, consent, and cybersecurity measures to ensure privacy, and provides necessary recommendations for the safe and effective use of AI technologies in the health sector.